The effect of stand-off distance on the failure of thin plates subjected to blast loads - Jacob, Neville (Department of Mechanical Engineering, 2024)
[page 31 missing] This investigation examines the effect of stand-off distance on the response of fully clamped circular plates subjected to blast loads. The experimental procedure consists of creating a blast load using disc shaped plastic explosive mounted onto a tube of required length. The length of the tube is the stand-off distance. Different lengths of tubes are used ranging from 25mm to 300mm. The internal diameter of the tube is 106mm. The dimension of the circular test plate is governed by the internal diameter of the tube. Hence all tests are conducted on 106mm diameter circular plates of thickness 1.9mm. The test plate is clamped between two clamping plates. The tube is screwed onto one of the clamping plates. The plate responses range from large inelastic deformation to complete tearing at the plate boundary. The deformed plate profile is dependent on stand-off distance. For stand-off distances ranging from 13mm to 40mm an inner dome atop a larger global dome is observed. In the case of stand-off distances ranging from 50mm to 300mm the deformed plate profile resembles a large global dome. The results show that mid-point deflection decreases with increasing stand-off distance for a given charge mass. The mid-point deflection drops rapidly from standoff distance of 13mm to 50mm, from stand-off distance of 75mm to 300mm the midpoint deflection asymptotes with similar values measured for a given charge mass. The results show two distinct loading regimes that occur depending on the stand-off distance between the explosive charge and the plate. At stand-off distances less than the plate radius of 53mm (13mm to 40mm}, the blast load is considered to be focused. This type of loading is referred to as localised loading. For stand-off distances greater than the plate radius (100mm to 300mm), the loading is said to be uniformly distributed over the entire plate area. At stand-off distances of 50mm to 75mm, the plate deformations exhibit a transition phase from localised loading to uniform loading. Theoretical and empirical analysis using Jones damage number, Nurick and Martin damage number and strain energy analysis to predict mid-point deflection of the deformed plate is performed. Appropriate modifications are made to above mentioned damages numbers and strain energy analysis to account for the effect of iii stand-off distance on plate deformation. The modified analyses show satisfactory correlation with experimental results.